Digitalization of the process of payment of settling allowances to servicemen of the Armed Forces of Ukraine and their families - Tsiukalo, Liudmyla; Tumanska, Marianna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Background. A component of the social security of the military personnel of the Armed Forces of Ukraine and their family members is a settling allowance paid to them in case of moving to a new place of military service in another settlement. Today there are a number of problems in this process of payment of this type of assistance. One of the factors that slows down the process of organizing the payment of relocation allowances to the military personnel of the Armed Forces of Ukraine today is a number of bureaucratic procedures in terms of collecting the relevant package of documents for the payment of relocation allowances, their approval and signing. In addition, one of the features of its payment is that the timeliness of receiving assistance also depends on the human factor. Therefore, the purpose of this article is to conduct a study on the possibility of digitalizing the process of paying the settling allowance to the military personnel of the Armed Forces of Ukraine and their families. Methods. The research methodology is based on the use of general scientific methods, in particular: analysis and synthesis, generalization, as well as a systematic approach to solving the tasks. The analytical method was used to identify theoretical approaches to the review and study of the legal framework governing the payment of allowances to the military personnel of the Armed Forces of Ukraine; the method of analogy was used for the proposed automated system for the process of payment of settling allowances to the military personnel. Results. It is proposed to develop and implement an automated system "Settling Allowances". The process of payment of lifting allowance to the military personnel using the automated system "Settling Allowances", which consists of eight stages, is described. Nine basic requirements for the automated system "Settling Allowances" are formed. Conclusions. An algorithm for digitalization of the process of payment of settling allowances to the military personnel of the Armed Forces of Ukraine has been developed and substantiated. Using this automated system will make the process of paying the settling allowance to the military personnel clear, fast and transparent.
Keywords: settling allowances, digitalization, military personnel, software, automated system